2005
DOI: 10.1016/j.enbuild.2004.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the energy-use effects of cool roofs on California commercial buildings

Abstract: Solar-reflective roofs stay cooler in the sun than solar-absorptive roofs. Such "cool" roofs achieve lower surface temperatures that reduce heat conduction into the building and the building's cooling load.The California Energy Commission has funded research in which Lawrence Berkeley National Laboratory (LBNL) has measured the electricity use and peak demand in commercial buildings to document savings from implementing the Commission's Cool Roofs program. The study seeks to determine the savings achieved by c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0
6

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(62 citation statements)
references
References 6 publications
0
56
0
6
Order By: Relevance
“…Heat transfer to the internal space by conduction is therefore reduced; the magnitude of the reduction will be determined by: A number of experimental and computational studies have been carried out to demonstrate the energy benefits of cool roofs in reducing energy demand in buildings in cooling dominated climates. A number of papers have been published for residential buildings [1,2,3,4,5,6], retail stores [7], and other commercial buildings [8,9]. Work has also been carried out outside the US.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heat transfer to the internal space by conduction is therefore reduced; the magnitude of the reduction will be determined by: A number of experimental and computational studies have been carried out to demonstrate the energy benefits of cool roofs in reducing energy demand in buildings in cooling dominated climates. A number of papers have been published for residential buildings [1,2,3,4,5,6], retail stores [7], and other commercial buildings [8,9]. Work has also been carried out outside the US.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, they concluded that the two most influential factors for the performance of roof reflective coatings are the U-value of the roof and the climatic conditions. Akbari et al [8] conducted experimental and numerical studies for 16 Californian climate zones, and reported energy savings of about 4.5-7.4 kWh/m 2 of conditioned roof area per year. They also differentiated between the investigated buildings, signifying the importance of building operation on the performance of roof reflective coatings.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Akbari et al [11] have monitored six commercial buildings in three different sites in California (USA) and demonstrated that the use of the cool roof technology is very effective in a hot-humid climate; an average reduction of 30 ∘ C is measured on the daily peak of the outer surface temperature of the roof, while the mean savings for air conditioning range from 42 Wh⋅m −2 ⋅day −1 to 81 Wh⋅m −2 ⋅day −1 , depending on the local weather conditions of the three sites considered and on the main features of the buildings monitored.…”
Section: Main Properties Of the Cool Materialsmentioning
confidence: 99%
“…The construction characteristics are shown in Table 2. For the study of the thermal behaviour of these two selected façades, the monitoring of each of the façades is carried out [4], [5]. The installed equipment consists of sensors of temperature, humidity, air speed and solar radiation.…”
Section: Conventional Façade With Insolation Inside the Supportmentioning
confidence: 99%